Vaccination dropout among children in Sub-Saharan Africa: Systematic review and meta-analysis - Natnael Atnafu Gebeyehu; Getachew Asmare Adela; Kirubel Dagnaw Tegegne; Belete Birhan Assfaw (Taylor & Francis Group, 2022)
Immunization is cost-effective preventive strategy for child morbidity and mortality. PubMed, Google Scholar, Scopus, Science Direct, and online institutional repository homes were searched. Data were extracted by Microsoft excel. Begg's rank test, and Egger's regression test was done. A pooled prevalence, Sub-group analysis, sensitivity analysis and meta-regression were conducted. A total of 12 articles were included in this study. The pooled prevalence of vaccination dropout was 26.06% (95% CI: 11.59, 30.53), I2 =91.2%. In sub-group analysis, Nigeria had the highest prevalence of immunization dropouts (33.59%). It was 18.01% and 29.25%, respectively, for published and unpublished research. Community-based studies and institutional-based studies also yield a prevalence of dropout 39.04% and 13.73% respectively. Dropout rate was 22.66% for sample sizes under 500 and 18.01% for sample sizes beyond 500. In Sub-Saharan Africa, the prevalence of vaccination dropout was high. Community education about vaccinations importance should be prioritized.